A template-free and low temperature method for the synthesis of mesoporous magnesium phosphate with uniform pore structure and high surface area. Issue 14 (27th March 2019) - Hövelmann, Jörn; Stawski, Tomasz M.; Besselink, Rogier; Freeman, Helen M.; Dietmann, Karen M.; Mayanna, Sathish; Pauw, Brian R.; Benning, Liane G.
Abstract : Thermal decomposition of crystalline struvite provides an efficient and well controllable method for the synthesis of mesoporous phosphates. Abstract : Mesoporous phosphates are a group of nanostructured materials with promising applications, particularly in biomedicine and catalysis. However, their controlled synthesis via conventional template-based routes presents a number of challenges and limitations. Here, we show how to synthesize a mesoporous magnesium phosphate with a high surface area and a well-defined pore structure through thermal decomposition of a crystalline struvite (MgNH4 PO4 ·6H2 O) precursor. In a first step, struvite crystals with various morphologies and sizes, ranging from a few micrometers to several millimeters, had been synthesized from supersaturated aqueous solutions (saturation index (SI) between 0.5 and 4) at ambient pressure and temperature conditions. Afterwards, the crystals were thermally treated at 70–250 °C leading to the release of structurally bound water (H2 O) and ammonia (NH3 ). By combining thermogravimetric analyses (TGA), scanning and transmission electron microscopy (SEM, TEM), N2 sorption analyses and small- and wide-angle X-ray scattering (SAXS/WAXS) we show that this decomposition process results in a pseudomorphic transformation of the original struvite into an amorphous Mg-phosphate. Of particular importance is the fact that the final material is characterized by a very uniform mesoporous structure with 2–5 nm wide pore channels, a large specific surface area of up to 300 m 2 g −1 and a total pore volume of up to 0.28 cm 3 g −1 . Our struvite decomposition method is well controllable and reproducible and can be easily extended to the synthesis of other mesoporous phosphates. In addition, the so produced mesoporous material is a prime candidate for use in biomedical applications considering that magnesium phosphate is a widely used, non-toxic substance that has already shown excellent biocompatibility and biodegradability.